2022
DOI: 10.1039/d1gc04243b
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoric acid-modified commercial kieselguhr supported palladium nanoparticles as efficient catalysts for low-temperature hydrodeoxygenation of lignin derivatives in water

Abstract: Efficient production of high value-added chemicals and biofuels via low-temperature chemoselective HDO of lignin derivatives in water is still of challenge. Here, we construct a low-cost, active and stable Pd/PCE...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…关于催化醛类的还原, 已报道了 Ni [9] 、 Cu [10] 、 Co [11] 、 Pt [12] 、Au [13] 、Ru [14] 、Ir [15] 、Ru [16] 和 Pd [17][18][19][20] 众所周知, 载体的性质影响金属的状态、试剂的吸 附性质和传质过程, 合适的载体可以提升加氢反应的活 性. 现已有碳 [21] 、 聚合物 [22] 、 Al 2 O 3 [23] 、 介孔二氧化硅 [24] 、 沸石 [25] 、碳纳米管 [26] 、金属-有机框架材料(MOF) [27] 、 石墨烯 [28][29][30] 等载体应用于负载 Pd 纳米颗粒.…”
Section: 引言unclassified
“…关于催化醛类的还原, 已报道了 Ni [9] 、 Cu [10] 、 Co [11] 、 Pt [12] 、Au [13] 、Ru [14] 、Ir [15] 、Ru [16] 和 Pd [17][18][19][20] 众所周知, 载体的性质影响金属的状态、试剂的吸 附性质和传质过程, 合适的载体可以提升加氢反应的活 性. 现已有碳 [21] 、 聚合物 [22] 、 Al 2 O 3 [23] 、 介孔二氧化硅 [24] 、 沸石 [25] 、碳纳米管 [26] 、金属-有机框架材料(MOF) [27] 、 石墨烯 [28][29][30] 等载体应用于负载 Pd 纳米颗粒.…”
Section: 引言unclassified
“…Vanillin is a typically lignin-derived aldehyde that can be manufactured on an industrial scale from biomass and converted into 2-methoxy-4-methylphenol (MMP), which has versatile applications in the fragrance industry and shows promise as an intermediate compound for pharmaceuticals. , To date, a considerable number of effective catalysts have been explored for the hydrodeoxygenation (HDO) of vanillin. However, most of them used noble metals as the main component, resulting in their application being limited by high prices, which has drawn attention to reusable earth-abundant transition metal-based catalysts. …”
Section: Introductionmentioning
confidence: 99%
“…Vanillin (VAN) is regarded as a typical platform molecule derived from lignin. Selective conversion of VAN to 2-methoxy-4-methylphenol (MMP) has recently gained great attention since the produced MMP can be used as a promising substrate in biofuels and pharmaceuticals. Many heterogeneous Pd-based catalysts have been designed for the efficient production of MMP from VAN. ,, Zhang et al reported that >99% selectivity of MMP was obtained from VAN catalyzed by a 2.0 wt % Pd@NH 2 -UiO-66 catalyst at 100 °C for 1 h, and such an excellent catalytic performance was attributed to the synergistic catalysis between Pd nanoparticles (NPs) and the special metal–organic framework carrier . Lv et al reported that >99% MMP selectivity was achieved over a superhydrophilic mesoporous sulfonated melamine-formaldehyde catalyst at 110 °C for 2 h .…”
Section: Introductionmentioning
confidence: 99%